Sequencing of unit operations for integral and sustainable peanut processing (Research, Society and Development, 2020)
The most used biomass are wood, sugar cane, paper, rice husk, and peanut. Based on the concept of sustainability and waste reduction, the full utilization of biomass is an alternative capable of providing people with a better nutritional intake, improving the economy related to biomass and the ecological relationship between man and the environment. So, the aim of this work was the sustainable use the biomass, the peanut, through multiple unit operations. Thus, the material went through several processes as the grinding process, where it was possible to obtain immediate analysis data (moisture content, ash content, volatile content and fixed carbon) and particle size. Then, drying was performed employing solar energy and the drying efficiency was obtained. Infrared and greenhouse tests were performed in the laboratory to determine the drying and humidity curves. After drying, it was also carried out the oil extraction using ethanol as solvent heated by solar energy. After that, the residual cake was used as the adsorbent material in the dye removal by adsorption in a fixed bed. So, the dye-impregnated adsorbent has undergone a process of pyrolysis in order to form fine coal, bio-oil, and gases. With products and by-products of each process, it was possible to generate the infrared spectrum of each. Therefore, it is shown how the integral use of peanut as biomass is possible, using chemical engineering sustainable processes, and how it may contribute to the reduction of the pollution and to the reduction of waste production.